Answers

The Brainliest Answer!
2015-03-05T15:37:54+05:30
For (3,4) 
take x=3 nd y= 4 so.. 3y = ax +7
                                3 × 4 = a × 3 + 7
                              ⇒ 12 = 3a  + 7
                              ⇒  12 - 7 = 3a
                              ⇒  5 = 3a
                              ⇒ 5÷ 3 = a
                              ⇒ a = 1.67

for (1,2)  as per above ⇒ a= -1
for (2,-3) as per above ⇒ a= -8
2 5 2
Comment has been deleted
Comment has been deleted
mark me best
Comment has been deleted
Well for theae types of questions you only need 1 point to solve
2015-03-05T15:43:41+05:30
3y=ax+7 Take the point (3,4) Put x=3 and y=4 3*4=a*3+7 12=3a+7 3a=5 a=5/3
0